Isolation of Extended-Spectrum β-lactamase- (ESBL-) Producing Escherichia coli and Klebsiella pneumoniae from Patients with Community-Onset Urinary Tract Infections in Jimma University Specialized Hospital, Southwest Ethiopia - Mengistu Abayneh; Getnet Tesfaw; Alemseged Abdissa (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Klebsiella pneumoniae and Escherichia coli are the major extended-spectrum β-lactamase- (ESBL-) producing organisms increasingly isolated as causes of complicated urinary tract infections and remain an important cause of failure of therapy with cephalosporins and have serious infection control consequence. Objective. To assess the prevalence and antibiotics resistance patterns of ESBL-producing Escherichia coli and Klebsiella pneumoniae from community-onset urinary tract infections in Jimma University Specialized hospital, Southwest Ethiopia, 2016. Methodology. A hospital-based cross-sectional study was conducted, and a total of 342 urine samples were cultured on MacConkey agar for the detection of etiologic agents. Double-disk synergy (DDS) methods were used for detection of ESBL-producing strains. A disc of amoxicillin + clavulanic acid (20/10 µg) was placed in the center of the Mueller–Hinton agar plate, and cefotaxime (30 µg) and ceftazidime (30 µg) were placed at a distance of 20 mm (center to center) from the amoxicillin + clavulanic acid disc. Enhanced inhibition zone of any of the cephalosporin discs on the side facing amoxicillin + clavulanic acid was considered as ESBL producer. Results. In the current study, ESBL-producing phenotypes were detected in 23% (n = 17) of urinary isolates, of which Escherichia coli accounts for 76.5% (n = 13) and K. pneumoniae for 23.5% (n = 4). ESBL-producing phenotypes showed high resistance to cefotaxime (100%), ceftriaxone (100%), and ceftazidime (70.6%), while both ESBL-producing and non-ESBL-producing isolates showed low resistance to amikacin (9.5%), and no resistance was seen with imipenem. In the risk factors analysis, previous antibiotic use more than two cycles in the previous year (odds ratio (OR), 6.238; 95% confidence interval (CI), 1.257–30.957; p = 0.025) and recurrent UTI more than two cycles in the last 6 months or more than three cycles in the last year (OR, 7.356; 95% CI, 1.429–37.867; p = 0.017) were found to be significantly associated with the ESBL-producing groups. Conclusion. Extended-spectrum β-lactamases- (ESBL-)producing strain was detected in urinary tract isolates. The occurrence of multidrug resistance to the third-generation cephalosporins, aminoglycosides, fluoroquinolones, trimethoprim-sulfamethoxazole, and tetracyclines is more common among ESBL producers. Thus, detecting and reporting of ESBL-producing organisms have paramount importance in the clinical decision-making.